Low cost, semi-automated hybrid bioreactor system for clean plant production of horticultural crops - Mishra, Maneesh; Damodaran, T; Verma, Anil Kumar; Rajan, Shailendra (Indian Horticulture, 2026)
Temporary immersion system (TIS) bioreactors for micropropagation of fruit crops have emerged as an ideal choice due to reduced production costs, rapid biomass accumulation, substantially higher multiplication rates, prevention of hyperhydricity through improved gas exchange, and ease of automation. This paper provides a detailed overview of micro-propagation of fruit crops using different TIS bioreactors.